Deforestation in the State of Amazonas: an econometric analysis (Research, Society and Development, 2022)
Deforestation in the Amazon Rainforest is one of the main environmental problems in the world today, due to its great importance for the environment. This deforestation causes extinction of plant and animal species, bringing irreparable damage to the Amazonian ecosystem. Some human actions are preponderant in this sense as the development of agricultural and livestock activities. Today, it is estimated that more than 83% of deforested areas have this purpose. The region of the state of Amazonas has 62 municipalities, of which the municipalities located to the south of the state suffer in terms of environmental degradation n due to the advance of the Agricultural and Livestock Frontier, most of the deforested areas being destined to the cultivation of soybeans and livestock. In the light of the above, the present study proposes to analyze, through the simple linear regression econometric tool, the level of impact of the variable cattle breeding on deforestation rate, using data from all municipalities, in a more specific way to measure the degree of influence of the variables. The results show that there is influence of livestock production on deforestation rate, therefore, the model can serve as reference to analyze the future behavior of the dependent variable, taking into account the assumptions of the model.